Urgensi dan Penerapan Konsep Cyber Notary di Masa Pandemi Covid-19 - Siti Malikhatun Badriyah; Intan Nur Baiti (Notarius, 2023)
AbstractCyber Notary concept is alternative that can be used Notary to work and making transactions during the pandemic. Article 15 paragraph (3)UUJN provides opportunities application of Cyber Notary concept where Notary can use functions and authority based on technology, such as making deeds and conducting certification by electronic. The purpose of this study is to analyze and describe reasons Cyber Notary concept cannot be applied in Covd-19 pandemic situation and the opportunities implementng Cyber Notary concept related to Notary's authorty in Notary Regulations. The method used is normative legal research by conducting legal analysis based on study from legislation and literature of Cyber Notary. It was concluded that the factor meaning of "essence" of authentic deeds, communicaton tools and internet networks were not evenly distributed, prone to abuse and the existence of conflicting norms between UUJN and UU TE as reason that Cyber Notary could not be applied. Opportunities for implementation of Cyber Notary are very open but contraned about regulation of Cyber Notary has not been further regulated so implementaton of Cyber Notary has not been perfect.Keywords: cyber notary; notary; covidAbstrakKonsep Cyber Notary merupakan suatu alternatif yang dapat digunakan dan memudahkan transaksi pekerjaan Notaris di masa pandemi. Pasal 15 ayat (3) UUJN memberikan peluang penerapan konsep Cyber Notary. Notaris dapat melakukan fungsi dan wewenang berbasis teknologi, misalnya membuat akta dan melakukan sertifikasi secara elektronik. Tujuan dari penelitian ini adalah untuk menganalisis dan mendeskripsikan alasan konsep Cyber Notary belum dapat diaplikasikan guna menyikapi situasi pandemi Covid-19 serta peluang penerapan konsep Cyber Notary terkait dengan kewenangan Notaris dalam Undang-Undang Jabatan Notaris. Metode yang digunakan adalah penelitian hukum normatif dengan melakukan analisa hukum berdasarkan pengkajian bahan yang berasal dari Peraturan Perundang-Undangan dan bahan literatur terkait konsep Cyber Notary. Melalui hasil penelitian didapatkan kesimpulan bahwa faktor makna “esensi” akta otentik, alat komunikasi dan jaringan internet yang belum merata, rawan disalahgunakan serta adanya pertentangan norma antara UUJN dan UU ITE sebagai alasan bahwa Cyber Notary belum dapat diterapkan. Peluang penerapan Cyber Notary sangat terbuka namun terkendala terkait belum adanya pengaturan lebih lanjut sehingga penerapan Cyber Notary belum berjalan sempurna.Kata kunci: cyber notary; notaris; covid